BUDAYA MERANTAU MASYARAKAT DAN PERMASALAHAN PENDAFTARAN PEMILIH PADA PILKADA DI SUMATERA BARAT - Mega Ardilla; Asrinaldi Asrinaldi (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2018)
An accurate, comprehensive and up-to-date voter list is an absolute prerequisite that must fulfill in carrying out electoral democracy. The existence of a correct voter list will improve the quality of the democratic electoral process by opening the most extensive possible space for citizens to exercise their right to vote. The purpose of this study was to find out the cultural implications of migrating the community in Lubuk Tarok sub-district to voter registration with the Dejure pattern. This research was carried out with qualitative methods through in-depth interviews with various informants equipped with existing documents. The results of this study show that due to the de jure pattern in voter registration has caused a large number of voters registered in the permanent voter list, but the voters are not by the KTP address. It is due to the wander culture in the Lubuk Tarok sub-district. Many of the residents of Lubuk Tarok are wandering out, but their population administration still listed in the Tarok. It is caused by many voting invitations to be returned by KPPS because there were no voters registered in the voter list. Also, this also has implications for the low level of voter participation on election day in the Lubuk Tarok sub-district.